Analyzing Job Motivation Level of High School Teachers in Turkey - Recepoğlu, Ergün (Elsevier BV, 2014)
AbstractThe aim of this research is to analyze job motivation level of high school teachers in Turkey. This is a descriptive research in the survey model. The population of the study is teachers who work in high schools in Karabük and Sinop. As a data collection instrument “Job Motivation Scale” developed by Aksoy (2006) was used. The frequency, percentage, arithmetical mean and standard deviation of the answers were calculated. Independent t-Test and One-Way ANOVA were performed to analyze the data. According to research findings, teachers have the highest motivation in dimension of commitment to job and the lowest level of motivation in the dimension of integration with the job. Job motivation level of teachers in high schools shows a significant difference in terms of age, tenure of office and education level while motivation of teachers do not show a significant difference in terms of teachers’ gender.
Keywords: high school; Job motivation; teacher; 4. Education